Peran Orang Tua Dalam Mendorong Prestasi Non Akademik Siswa Di SDN Balongbesuk Jombang - Usthufiyah, Farida; Fitra Raharja , Hawwin; Dwinata, Anggara (IJPSE Indonesian Journal of Primary Science Education, 2024)
The family, particularly parents, plays a pivotal role in instilling life values in their children to achieve meaningful life goals. This study aims to explore parental parenting styles concerning non-academic achievements among students at SDN Balongbesuk Jombang. A qualitative case study approach was employed, utilizing data collected through observation, interviews, and documentation. Parents of non-academic achievers and the students themselves served as data sources. The findings reveal that parents employ a "Democratic" parenting style, which is perceived as warm and supportive for children. Parental efforts to support their children's achievements include granting them freedom of choice and involvement in extracurricular activities, providing motivation and support, and allocating time to support their participation in competitive events. The majority of non-academic achievers positively receive this parenting style. In conclusion, the "Democratic" parenting style is found to be effective in supporting non-academic student achievements.